Narrowing down dimensions of e-learning readiness in continuing vocational education — perspectives from the adult learner - Loock, Vanessa Stefanie; Fleischer, Jens; Scheunemann, Anne; Froese, Linda; Teich, Katharina; Wirth, Joachim (Frontiers in Psychology, 2022)
Although e-learning has become an important feature to promote learning experience, still little is known about the readiness of adult learners for e-learning in continuing vocational education. By exploring perceived challenges and benefits, it was our aim to identify dimensions that define e-learning readiness. Therefore, we conducted a study design with qualitative and quantitative components. It consisted of both, semi-structured interviews, as well as an online survey regarding biography, personality, learning behavior, and general attitudes toward e-learning. The continuing vocational education course that we were investigating comes from the field of project management. The learner group was heterogeneous regarding their biographical and occupational background. Our results suggest several dimensions of e-learning readiness which are namely: motivation, learning strategies/regulation, attitudes toward learning, and personality-associated aspects as well as digital literacy. These findings are in line with previous research to only some extent, but reveal the necessity to redefine single dimensions of e-learning readiness to develop an inventory that is generalizable for different adult learner groups. Based on these assumptions a new measure for e-learning readiness needs to be proposed in future research as a next step.